Economic Modelling of Screen-and-Treat Strategies for Brazilian Women at Risk of Hereditary Breast and Ovarian Cancer - Julia Simoes Correa-Galendi; Maria del Pilar Estevez Diz; Stephanie Stock; Dirk Müller (Applied Health Economics and Health Policy, 2020)
Background: Clinical evidence supports the use of genetic counselling and BRCA1/2 testing for women at risk for hereditary breast and ovarian cancer. Currently, screen-and-treat strategies are not reimbursed in the Brazilian Unified Healthcare System (SUS). The aim of this modelling study was to evaluate the cost effectiveness of a gene-based screen-and-treat strategy for BRCA1/2 in women with a high familial risk followed by preventive interventions compared with no screening. Methods Adopting the SUS perspective, a Markov model with a lifelong time horizon was developed for a cohort of healthy women aged 30~years that fulfilled the criteria for BRCA1/2 testing according to the National Comprehensive Cancer Network (NCCN) guideline. For women who tested positive, preventive options included intensified surveillance, risk-reducing bilateral mastectomy and bilateral salpingo-oophorectomy. The Markov model comprised the health states `well', `breast cancer', `death' and two post-cancer states. Outcomes were the incremental costs per quality-adjusted life-year (QALY) and the incremental costs per life-year gained (LYG). Data were mainly obtained by a literature review. Deterministic and probabilistic sensitivity analyses were performed to assess the robustness of the results. Results In the base case, the screen-and-treat strategy resulted in additional costs of 3515 Brazilian reais (R) (US1698) and a gain of 0.145 QALYs, compared with no screening. The incremental cost-effectiveness ratio (ICER) was R24,263 (US21,724) per QALY and R27,258 (US24,405) per LYG. Applying deterministic sensitivity analyses, the ICER was most sensitive to the probability of a positive test result and the discount rate. In the probabilistic sensitivity analysis, a willingness to pay of R25,000 per QALY gained for the screen-and-treat strategy resulted in a probability of cost effectiveness of 80%. Conclusion Although there is no rigorous cost-effectiveness threshold in Brazil, the result of this cost-effectiveness analysis may support the inclusion of BRCA1/2 testing for women at high-risk of cancer in the SUS. The ICER calculated for the provision of genetic testing for BRCA1/2 approximates the cost-effectiveness threshold proposed by the World Health Organization (WHO) for low- and middle-income countries.
Keywords: 610; Pharmacoeconomics and Health Outcomes; Quality of Life Research; Health Economics; Health Administration; Public Health